Increasing the Radioiodine Dose Does Not Improve Cure Rates in Severe Graves' Hyperthyroidism: A Clinical Trial with Historical Control - Dora, Jose Miguel (Hindawi Publishing Corporation, 2013)
Objective. It is generally accepted that higher doses of radioiodine ((131)I) improve cure rates in Graves' disease (GD). In this trial we sought to evaluate whether very high (131)I doses increase the efficacy of treatment in severe GD. Design. Clinical trial with historical control. Patients with GD and a goiter ≥48 mL were eligible for the study. The patients in the contemporaneous intervention cohort were treated with 250 μCi of (131)I/mL thyroid tissue, corrected by 24-RAIU values (Group 1; n = 15). A subgroup of patients with GD and a goiter ≥48 mL who were treated with 200 μCi of (131)I/mL/24-RAIU in a previously published randomized controlled trial served as a historical control group (Group 2; n = 15). The primary outcome evaluated was the one-year cure rate. Results. There were no significant baseline differences regarding age, gender, body mass index, smoking status, pretreatment with methimazole, thyroid volume, or thyroid hormone levels of the two treatment groups. The cumulative 12-month cure rate for the patients in Group 1 was 66.6%, a figure similar to the 12-month cure rate observed in Group 2 (60.0%; P = 0.99). Conclusions. Our results suggest that increasing the (131)I dose does not improve cure rates in severe GD. This trial is registered with ClinicalTrials.gov NCT01039818.